2021
DOI: 10.7575/aiac.ijels.v.9n.2p.136
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Secondary School Students’ Writing Attitudes and Anxiety and Writing Disposition

Abstract: Literacy is an important result of language teaching. Language skills are like the pieces of a whole. The accurate acquisition of these skills, which are needed to be used effectively by individuals both in their social and educational life, is equally valuable. Writing is a skill that is acquired and developed mostly during the learning process among these skills. Writing requires not only recognizing the letters and language rules but also understanding and internalizing oneself and the environment. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
2
1
Order By: Relevance
“…Thus, their performance in writing will be in line with the level of anxiety they have whether it is good or bad. Not only that, this study also showing different result from Karahan (2021) asserted that the writing anxiety had a significant difference on the students' writing grade and the students who have anxiety in a high level. Therefore, it can be concluded that no matter how high and low the students' anxiety level in writing, if they still have really good writing ability and understanding, they will always perform greatly in doing their writing tasks.…”
Section: The Effect Of Students' Writing Anxiety On the Students' Wri...contrasting
confidence: 56%
See 1 more Smart Citation
“…Thus, their performance in writing will be in line with the level of anxiety they have whether it is good or bad. Not only that, this study also showing different result from Karahan (2021) asserted that the writing anxiety had a significant difference on the students' writing grade and the students who have anxiety in a high level. Therefore, it can be concluded that no matter how high and low the students' anxiety level in writing, if they still have really good writing ability and understanding, they will always perform greatly in doing their writing tasks.…”
Section: The Effect Of Students' Writing Anxiety On the Students' Wri...contrasting
confidence: 56%
“…It includes several kinds of disordered thoughts, increased physical excitement, and inappropriate behaviors. Likewise, it is a negative condition where students experience tension, nervousness, fear or even feel stomach cramps before or during the writing process since it relates to the students' psychological and physiological state (Başkan, 2021;Karahan, 2021;Syarifudin, 2020;Turkben, 2021). Those conditions can be happened because several things (Wahyuni et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Also, their willingness to practice and improve their organizational skills suggests they'll become stronger and more confident writers over time. Karahan (2021) highlighted that people may have different motivations and varying levels of success when it comes to writing due to differences in their interests and needs. Therefore, personal differences, interests, and demands may have an impact on the development and improvement of writing abilities.…”
Section: Resultsmentioning
confidence: 99%